Perception Scale of Online Learning in the Indonesian Context During the Covid-19 Pandemic: Psychometric Properties Based on the Rasch Model - Nursulistyo, Eko; Indratno, Toni Kus; Dwiastuti, Ety; Arifiyanti, Fitria; Dina Puspitasari, Ariati; Abdullah, Nurul Syafiqah Yap binti; Sukarelawan, Moh. Irma (Universitas Ahmad Dahlan, 2022)
This study aims to evaluate the psychometric properties of students' perception scales about online learning during the Covid-19 pandemic in Indonesian culture. This study involved 176 students (Male = 54% and Female = 46%) at the junior and senior high school levels from public schools in Yogyakarta, Indonesia. The age of the respondents ranged from 11 to 17 years, with a mean of 13.5 years and a standard deviation of 1.4 years. The online learning perception scale adopts 16 items developed by Bhagat and colleagues. The psychometric properties of the scale were evaluated based on the reliability of the person and item, the suitability of the Rasch model, the functionality of using a 5-point rating scale, and its unidimensionality. The analysis results show that the scale has good consistency and performance in the Indonesian context. Sixteen items are a good fit for the model and are unidimensional. The 4-point Likert rating scale is more effective than the original 5-point rating scale. So, 16 items in POSTOL have adequate psychometric properties to be used on students in Indonesia.